Assessment of biodiversities and spatial structure of Zarivar Wetland in Kurdistan Province, Iran - MAHDI REYAHI KHORAM; KAMAL HOSHMAND (Society for Indonesian Biodiversity, 2012)
Reyahi-Khoram M, Hoshmand K. 2012. Assessment of biodiversities and spatial structure of Zarivar Wetland in Kurdistan Province, Iran. Biodiversitas 13: 130-134. Wetlands are valuable ecosystems that occupy about 6% of the world’s land surface. Iran has over 250 wetlands measuring about 2.5 million hectares. Zarivar wetland (ZW) is the only natural aquatic ecosystem in Kurdistan province in Iran. The present research was carried out during 2009 through 2010 with the aim of recognizing the capabilities and limitations of ZW through documentary, extensive field visits and also direct field observations during the years of study. Geographic Information System (GIS) has been used to evaluate the land as a main tool. The results of this research showed that ZW has a great talent regarding diversity of bird species and the ecological status of wetland has caused the said wetland welcome numerous species of birds. The results of this research showed that industrial pollutions are not considered as threats to the wetland but evacuation of agricultural runoff and development of Marivan city toward the wetland and the resulting pollution load could be introduced as an important part of thewetland threats. It is recommended to make necessary studies in the field of various physical and biological parameters of the wetland, and also the facing threats and opportunities.Key words: aquatic, biodiversity, environment, wetland, Zarivar